UPAYA PENINGKATAN PENGETAHUAN MENGENALI TANDA BAHAYA NIFAS DAN BAYI BARU LAHIR - Elsa Noftalina; Wiwit Triastuti (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2021)
Background The postpartum period is an important period in determining the health status of the mother and baby. One of the factors causing maternal death occurs after delivery or within the first 24 hours of the puerperium. The period of the Covid 19 pandemic that has not ended has had various impacts on health problems, especially obstetrics. Local Area Monitoring of Maternal and Child Health in various indicators, especially postpartum visits, has experienced a downward trend and several regions have not met the target achievement. This can be caused by a lack of information from mothers in carrying out examinations during the pandemic. The purpose of this service is to increase the knowledge of postpartum mothers about the danger signs of childbirth and newborns. The method used in this service is counseling with the lecture and discussion method. The media used was the Googlemeet video teleconference. Participants in the activity were postpartum mothers who were in RW 3 in the working area of the Central Siantan Health Center. This community service was carried out on October 2nd, 2020. The results was the activity showed that there was an increase in knowledge and postpartum mothers regarding the danger signs of childbirth and newborns, even though there were several obstacles to doing counseling through the googlemeet media, namely not all postpartum mothers had smartphones and networks that were not smooth due to weather disturbances.